Multiple pulmonary micronodules in a patient with Crohn's disease. (5th August 2010) - Abbas, S A; Syed, Y I; Dushianthan, A; Barry, S
Abstract : Sarcoidosis is a terrific mimicker and can present in many different ways. The case of a middle-aged woman with Crohn's disease who attended the gastroenterology clinic for routine follow-up is presented. She had dry cough and breathlessness for a few weeks. A chest x-ray showed scattered multiple bilateral pulmonary micronodules. This finding on her chest x-ray posed a diagnostic challenge, especially in view of the fact that she was previously treated with immunosuppressants to control her Crohn's disease. A diagnosis of sarcoidosis was established by various tests including lung biopsy, which showed non-caseating granulomas. Within a few weeks of beginning systemic steroid treatment, improvement was noticed in symptoms and lung function tests.